Effect of Oral Nirmatrelvir on Long COVID Symptoms: 4 Cases and Rationale for Systematic Studies - Michael Peluso; Khamal Anglin; Matthew S. Durstenfeld; Jeffrey N. Martin; J. Daniel Kelly; Priscilla Y. Hsue; Timothy J. Henrich; Steven G. Deeks (Case Western Reserve University, 2022)
Background: Efforts to understand the impact of SARS-CoV-2 variants, vaccine status, and treatment on the development and persistence of Long COVID have intensified.  Methods: We report 4 sequential cases from a post-COVID cohort study demonstrating variability in outcomes following differentially timed nirmatrelvir therapy, received as part of clinical care.  Results: In the first case, the participant experienced symptomatic rebound and developed Long COVID despite early initiation of antiviral therapy. In the next 2 cases, participants reported improvement in persistent COVID symptoms when nirmatrelvir was taken 25 and 60 days following initial symptom onset. In the final case, an individual with presumed Long COVID for 2 years reported substantial improvement in chronic symptoms when taking nirmatrelvir following SARS-CoV-2 re-infection.  Conclusions: These anecdotes suggest that systematic study of antiviral therapy for Long COVID is warranted.